2022
DOI: 10.3390/cells11121913
|View full text |Cite
|
Sign up to set email alerts
|

Thwarting of Lphn3 Functions in Cell Motility and Signaling by Cancer-Related GAIN Domain Somatic Mutations

Abstract: Cancer progression relies on cellular transition states accompanied by changes in the functionality of adhesion molecules. The gene for adhesion G Protein-Coupled Receptor latrophilin-3 (aGPCR Lphn3 or ADGRL3) is targeted by tumor-specific somatic mutations predominantly affecting the conserved GAIN domain where most aGPCRs are cleaved. However, it is unclear how these GAIN domain-altering mutations impact Lphn3 function. Here, we studied Lphn3 cancer-related mutations as a proxy for revealing unknown GAIN dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…6a) 19,70 . Recent work showed that ADGRL3 signaling through Gα 12/13 was impaired by the single-point cancer-related mutations S810L and E811Q 70 although the mutations had no effect on autoproteolysis and are not a part of the TA 19 . These observations suggested that GAIN domain could make transient interactions with the extracellular loops on the 7TM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6a) 19,70 . Recent work showed that ADGRL3 signaling through Gα 12/13 was impaired by the single-point cancer-related mutations S810L and E811Q 70 although the mutations had no effect on autoproteolysis and are not a part of the TA 19 . These observations suggested that GAIN domain could make transient interactions with the extracellular loops on the 7TM.…”
Section: Resultsmentioning
confidence: 99%
“…A low-resolution model of LK1 bound to ADGRL3 further confirms the intact LK1/ADGRL3 complex and presents a different orientation of the GAIN domain. Similarly, cancer-associated mutations that are shown to decrease the receptor activity also change the population of smFRET conformations, suggesting that a shift in the populations of conformations might underly reduction in receptor signaling 70 (Fig. 7a).…”
Section: Agonistic Antibodies and Disease Mutations At The Ecr-tm Int...mentioning
confidence: 94%
See 1 more Smart Citation
“…5) close to the GPS may now be tested in any model system based on their GRN index. Analogously, we can now assess the location of known pathological mutations: Avila-Zozaya et al have investigated cancer-related mutations in ADGRL3, with impacts on G 13 -signaling for K561N H1.51 , D798H S9.47 , S810L s9s10 and E811Q s9s10 , where the latter two residues correspond to the interaction region of the GAIN domain with the seventransmembrane domain 19,53 . Two mutations responsible for loss of surface expression in GPR56, causing bilateral frontoparietal polymicrogyria (BFPP), are the highly conserved C346S S10.47 and W349S S10.50 ref 6,72,73 .…”
Section: Discussionmentioning
confidence: 99%
“…As aGPCRs support structural cell positioning within a given tissue, they are attributed biological functions as diverse as cell migration, synapse formation, angiogenesis, differentiation and apoptosis to name a few [2][3][4][5][6] . The importance of aGPCRs in sustaining physiological functions was highlighted by their association with a plethora of human disorders for which receptor dysfunctions are thought to account for most of the underlying etiological factors 7,8 . Their involvement in such a wide range of physiological or pathophysiological events posit aGPCRs as potential pharmacological targets amenable to therapeutic use hence the heightened interest in studying their function.…”
Section: Introductionmentioning
confidence: 99%